Analysis of Internal Control of Debt Payment at Hotel X - PUTRI, I Gusti Ayu Deanita; TUWI , I Wayan; SUSANTI , Christina (Journal of Governance, Taxation and Auditing, 2025)
A good internal control system is required to minimize errors and fraud within a company. This study aims to determine the internal control of debt financing in the Accounts Payable department at Hotel X. Data collection was conducted through observation, interviews, questionnaires, and documentation. The data analysis technique used in this study is descriptive qualitative, by analyzing the implementation of internal control in the Accounts Payable department to determine whether it is in accordance with the five main components of COSO-based internal control. The results of this study indicate that internal control of debt payment at Hotel X Bali is considered very effective based on the Internal Control - Integrated Framework concept from COSO. However, there were still delays in debt payments to suppliers at Hotel X Bali in December 2024, which caused complaints from suppliers and other departments. This indicates that there is still one aspect of control that has not been running optimally, namely, in terms of information delivery and communication between departments. This is what the researcher then provided corrections and suggestions, one of which is to improve communication between units and increase control over staff, especially during the high season.